Compositional Engineering of Chitosan–Potato Starch–Kaolin Biocomposites: Tuning Physicochemical Properties for Wound Dressing Applications - Suryati Suryati; Rizka Mulyawan; Meriatna Meriatna; Cut Khairunnisa; Leni Maulinda; Fikri Hasfita (Malikussaleh University, Aceh, Indonesia, 2025)
An investigation has been made to predict the effects of various Kaolin fillers with different concentrations from 4 to 10 percent on the properties of Chitosan and Potato Starch Bio-composite for wound dressing applications. The procedure was to prepare the chitosan and starch in equal proportions, apply the filler to the hydrogel, dry it, and characterize it. The characterizations of the synthesized bio-composite were its absorption percentage, mechanical test, presented functional groups, and antibacterial test. It was found out that the bio-composite with the highest swelling percentage 6% Kaolin, showed 128.65% swelling. Moreover, the highest percentage of bio-composite absorption was 65.62% with 8% Kaolin added. In addition to that, adding 4% Kaolin produced the highest tensile strength with the value of 75.6 MPa. Besides, the most significant elongation percentage was 151.60% in the addition of 4% Kaolin. Qualitatively, the synthesized bio-composites exhibited functional groups of OH, alkynes, and carboxylic acid. Finally, the bio-composite with Kaolin filler significantly performed in antibacterial activities.